Using an inpatient portal to engage families in pediatric hospital care. (14th June 2016) - Kelly, Michelle M; Hoonakker, Peter L T; Dean, Shannon M
Abstract : Objective: Assess parent use and perceptions of an inpatient portal application on a tablet computer that provides information about a child's hospital stay. Methods: This cross-sectional study was conducted with parents of children hospitalized on a medical/surgical unit at a tertiary children's hospital. From December 2014 to June 2015, parents were provisioned a tablet portal application to use throughout the hospitalization. The portal includes real-time hospital vitals, medications, schedules, lab results, education, health care team pictures/roles, and request and messaging functionalities. Portal use information was gathered from tablet metadata. Parents completed discharge surveys on portal satisfaction, use, and impact on their information needs, engagement, communication, error detection, and care safety and quality. Data were analyzed using descriptive statistics and qualitative content analysis. Results: Over 6 months, 296 parents used the portal, sending 176 requests and 36 messages. No tablets were lost or damaged. The most used and liked features included vitals, medication list, health care team information, and schedules. Overall, parent survey respondents (90) were satisfied with the portal (90%), reporting that it was easy to use (98%), improved care (94%), and gave them access to information that helped them monitor, understand, make decisions, and care for their child. Many parents reported that portal use improved health care team communication (60%). Most perceived that portal use reduced errors in care (89%), with 8% finding errors in their child's medication list. Conclusions: Overall, parents were satisfied with the inpatient portal. Portals may engage parents in hospital care, facilitate parent recognition of medication errors, and improve perceptions of safety and quality.